Pharmacological underlying mechanisms of the anticancer effect of licorice: Bioinformatics and experimental verification - Mengqi Liu; Lingping Fu; Hao Fu; Yu Chen; Mengxia Wu; Hanchun Liu (KeAi Communications Co., Ltd., 2024)
Purpose: Cancer is the second leading cause of human mortality and has rapidly become a major global issue. According to traditional Chinese medicine (TCM) theory, the primary pathogenesis of cancer is the deficiency of ''vital Qi''. Licorice (Gancao in Chinese, GC) one of the oldest and the most frequently used herbs for tonifying Qi, is commonly integrated with other Chinese medicines to treat cancer in TCM clinical practice. GC extract, or its chemical components, are often utilized in cancer treatment. However, the molecular mechanisms underlying GC's therapeutic effects on cancer remain unclear. Our current study aimed to elucidate these mechanisms from the perspective of network pharmacology and experimental validation. Methods: We employed network pharmacology and bioinformatics to explore the anti-cancer mechanism, crucial targets, and kernel ingredients of GC. The significant targets and key ingredients (quercetin, glycyrrhetinic acid, and glucyrin) were substantiated using the Cancer Genome Atlas (TCGA) and Cell Counting Kit-8 (CCK-8) viability assay, respectively. Results: Our findings identified eight critical targets and key ingredients (quercetin, glycyrrhetinic acid, glucyrin) and suggested that GC's anti-cancer effects are primarily associated with modulation of the immune system, signal transduction, cell cycle, and gene expression. The efficacy of quercetin, glycyrrhetinic acid, glucyrin against Human A549 lung cancer cells was confirmed. Conclusion: This study comprehensively elucidates the mechanisms through which GC addresses cancer, leveraging network pharmacology and experimental validation. These insights contribute to identifying principal compounds and developing innovative drugs for cancer therapy.